2021
DOI: 10.3390/ijerph182312460
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Body and Body Dissatisfaction in Primary Education Children According to Gender and Age. A Cross-Sectional Study

Abstract: Body image (BI) is a trending topic of study since health problems derived from a negative perception of the body are increasing and affecting people of all ages, with an increasing incidence among children from the age of eight. The objective of this study was to evaluate the current perception of the body against the desired body and the degree of body satisfaction of Galician primary education students. A total of 355 students (167 boys (47%)) between 9 and 12 years old participated (mean = 10.53; SD = 0.84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
1
6
1
Order By: Relevance
“…People with low self-esteem want to achieve self-esteem by controlling food, weight or body shape, and according to Brockmeyer et al achieving low weight can be defined as winning, which is also strongly associated with excessive control over eating [ 54 ]. However, contrary to the results of our own research on body dissatisfaction, the study did not notice any major differences between the female and male sexes, and the results of the study showed similar dissatisfaction occurring in both sexes [ 55 ]. According to the authors, this may be due to the smaller number of studies on the male group.…”
Section: Discussioncontrasting
confidence: 99%
“…People with low self-esteem want to achieve self-esteem by controlling food, weight or body shape, and according to Brockmeyer et al achieving low weight can be defined as winning, which is also strongly associated with excessive control over eating [ 54 ]. However, contrary to the results of our own research on body dissatisfaction, the study did not notice any major differences between the female and male sexes, and the results of the study showed similar dissatisfaction occurring in both sexes [ 55 ]. According to the authors, this may be due to the smaller number of studies on the male group.…”
Section: Discussioncontrasting
confidence: 99%
“…At baseline, fewer than half (41 %) of pupils always felt good about their bodies, and 9 % of pupils never or rarely felt good about their bodies. Similar results were found in Spain, where 43 % of pupils of the same age (9-12 years old) were satisfied with their bodies (45) . In future research, an adapted version of the questionnaire Body Appreciation Scale-2 for children (BAS-2C) (37) could be a useful measure to get more specific information on children's body image.…”
Section: Discussionsupporting
confidence: 85%
“…A growing body of research indicates that body dissatisfaction is already prevalent during middle childhood ( Neves et al, 2017 ; Paxton and Damiano, 2017 ; Latiff et al, 2018 ; World Health Organization, 2020 ; Navarro-Patón et al, 2021 ). Sociocultural influences, are primarily targeted as potential risk factors in research on the development of body dissatisfaction ( Stice and Whitenton, 2002 ; McCabe and Ricciardelli, 2005 ; Cash and Smolak, 2011 ).…”
Section: Introductionmentioning
confidence: 99%